THE IMPACT OF POLITICAL CHANGE ON THE DYNAMICS OF CRIMINAL LAW REFORM (A COMPARATIVE STUDY OF POLITICAL RELATIONS AND THE IMPLEMENTATION OF CRIMINAL LAW IN THE PHILIPPINES) - Weko Satya Guntoro; Anang Puji Utama; Irwan Triadi (RADJA PUBLIKA, 2025)
In a political system which is interconnected between government departments and elements of society in a nation, there is always social interaction that influences each other. This influence has an impact on the configuration of interests formed in a legal product. Law is a means to achieve political goals, therefore in every stage of its formation and implementation there is a lot of partisanship from political stakeholders. In a democratic country, the supreme power is in the hands of the people which is manifested in a legislative institution with a periodic replacement cycle. However, competition between political groups is an inevitability that requires qualified regulation, including in emergency situations. One country that has a political system similar to Indonesia and has experienced disruptive politics and legal reform is the Philippines. Hopefully this study will create awareness for mitigation in dealing with similar emergency situations.